2012
DOI: 10.1016/j.bbamcr.2012.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic remodeling in iron-deficient fungi

Abstract: Eukaryotic cells contain dozens, perhaps hundreds, of iron-dependent proteins, which perform critical functions in nearly every major cellular process. Nutritional iron is frequently available to cells in only limited amounts; thus, unicellular and higher eukaryotes have evolved mechanisms to cope with iron scarcity. These mechanisms have been studied at the molecular level in the model eukaryotes Saccharomyces cerevisiae and Schizosaccharomyces pombe, as well as in some pathogenic fungi. Each of these fungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
93
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 100 publications
(151 reference statements)
9
93
0
6
Order By: Relevance
“…As a redox-active metal, iron is an important cofactor in a variety of enzymes that are intimately linked to essential cellular functions such as DNA synthesis, oxidative phosphorylation, and the biosynthesis of metabolites (10,36). Ironically, this same redox property allows iron to undergo Fenton-type chemical reactions that result in the production of hydroxyl radicals that can lead to cell death (8).…”
mentioning
confidence: 99%
“…As a redox-active metal, iron is an important cofactor in a variety of enzymes that are intimately linked to essential cellular functions such as DNA synthesis, oxidative phosphorylation, and the biosynthesis of metabolites (10,36). Ironically, this same redox property allows iron to undergo Fenton-type chemical reactions that result in the production of hydroxyl radicals that can lead to cell death (8).…”
mentioning
confidence: 99%
“…Studies on nonphotosynthetic unicellular organisms such as bacteria and yeast have suggested that programs exist to acclimate metabolism to Fe deficiency (Oglesby-Sherrousse and Murphy, 2013;Philpott et al, 2012). Compared to heterotrophs, photosynthetic organisms have to cope with a substantially higher demand for Fe because of the added Fe requirement of the chloroplast (for review, see BlabyHaas and Merchant, 2013).…”
mentioning
confidence: 99%
“…Aft1 and Aft2 play a central role in iron-dependent transcription activation of genes encoding components involved in cellular uptake and intracellular distribution of iron (9,10). Yap5 is involved in the detoxification of excess iron by inducing the transcription of, e.g., CCC1 encoding the only known iron importer into the vacuole, the major metal storage organelle in fungi (11,12).…”
mentioning
confidence: 99%